162k views
5 votes
Differentiate y = csc(x)cot(x).

User Griv
by
5.1k points

1 Answer

3 votes

Answer:


\displaystyle y' = - \csc (x) \big[ \cot^2 (x) + \csc^2 (x) \big]

General Formulas and Concepts:

Algebra I

Terms/Coefficients

  • Factoring

Functions

Calculus

Differentiation

  • Derivatives
  • Derivative Notation

Derivative Rule [Product Rule]:
\displaystyle (d)/(dx) [f(x)g(x)]=f'(x)g(x) + g'(x)f(x)

Explanation:

Step 1: Define

Identify.


\displaystyle y = \csc (x) \cot (x)

Step 2: Differentiate

  1. Derivative Rule [Product Rule]:
    \displaystyle y' = (d)/(dx)[\csc (x)] \cot (x) + \csc (x) (d)/(dx)[\cot (x)]
  2. Trigonometric Differentiation:
    \displaystyle y' = - \csc (x) \cot (x) \cot (x) + \csc (x) \big[ - \csc ^2 (x) \big]
  3. Simplify:
    \displaystyle y' = - \csc (x) \cot^2 (x) - \csc^3 (x)
  4. Factor:
    \displaystyle y' = - \csc (x) \big[ \cot^2 (x) + \csc^2 (x) \big]

Topic: AP Calculus AB/BC (Calculus I/I + II)

Unit: Differentiation

User Toastor
by
5.1k points